1988
DOI: 10.1093/oxfordjournals.jbchem.a122421
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Water in Conjunction with Plant Movement Visualized by NMR Imaging1

Abstract: The water distribution in the pulvinus of Mimosa can be visualized by an NMR imaging technique. After stimulation of a Mimosa plant, water in the lower half of the main pulvinus disappeared, the water previously contained in this area seeming to be transferred to the upper half of the main pulvinus. Movement of the water in conjunction with Mimosa movement was visualized sequentially by a non-invasive NMR imaging procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 0 publications
5
45
0
1
Order By: Relevance
“…One of the most remarkable results is the immediate disappearance of water in the lower part of the pulvinus as it leans down25. This result implies that the M. pudica motion is deeply related to water transport.…”
Section: Resultsmentioning
confidence: 94%
“…One of the most remarkable results is the immediate disappearance of water in the lower part of the pulvinus as it leans down25. This result implies that the M. pudica motion is deeply related to water transport.…”
Section: Resultsmentioning
confidence: 94%
“…This movement is caused by a loss of turgor pressure in one half of the pulvinus (extensor [7]), which is located at the base of each primary petiole, pinna, and pinnule (leaflet) [6]. Nuclear magnetic resonance (NMR) imaging demonstrated that water is translocated from the extensor half to the other half (flexor [7]) of the pulvinus during the movement [8]. At the cellular level, individual “motor cells” in the extensor half of the pulvinus shrink following outflow of intracellular water [9], [10], which is accompanied by a large efflux of K + and Cl - ions [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…because of groups of antagonistic specialized cells that are located in 'hinges' called pulvini. Upon stimulation, the cells on one side of the pulvinus swell and those on the other side shrink, thereby actuating the movement (Tamiya et al 1988).…”
Section: Introductionmentioning
confidence: 99%